Predictors of Long‐Term Renal Outcome in Lupus Nephritis Trials: Lessons Learned from the Euro‐Lupus Nephritis Cohort. Issue 5 (May 2015) - Dall'Era, Maria; Cisternas, Miriam G.; Smilek, Dawn E.; Straub, Laura; Houssiau, Frédéric A.; Cervera, Ricard; Rovin, Brad H.; Mackay, Meggan
<x xml:space="preserve">Abstract</x> Objective There is a need to determine which response measures in lupus nephritis trials are most predictive of good long‐term renal function. We used data from the Euro‐Lupus Nephritis Trial to evaluate the performance of proteinuria, serum creatinine (Cr), and urinary red blood cells (RBCs) as predictors of good long‐term renal outcome. Methods Patients from the Euro‐Lupus Nephritis Trial with proteinuria, serum Cr, and urinary RBC measurements at 3, 6, or 12 months and with a minimum of 7 years of followup were included (n = 76). We assessed the ability of these clinical biomarkers at 3, 6, and 12 months after randomization to predict good long‐term renal outcome (defined as a serum Cr value ≤1.0 mg/dl) at 7 years. Receiver operating characteristic curves were generated to assess parameter performance at these time points and to select the best cutoff for individual parameters. Sensitivity and specificity were calculated for the parameters alone and in combination. Results A proteinuria value of <0.8 gm/day at 12 months after randomization was the single best predictor of good long‐term renal function (sensitivity 81% and specificity 78%). The addition of serum Cr to proteinuria as a composite predictor did not improve the performance of the outcome measure; addition of urinary RBCs as a predictor significantly decreased the sensitivity to 47%. Conclusion This study demonstrates that the level of proteinuria at 12 months is the individual best predictor of long‐term renal outcome in patients with lupus nephritis. Inclusion of urinary RBCs as part of a composite outcome measure actually undermined the predictive value of the trial data. We therefore suggest that urinary RBCs should not be included as a component of clinical trial response criteria in lupus nephritis.